1996
DOI: 10.1083/jcb.132.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Onset of re-epithelialization after skin injury correlates with a reorganization of keratin filaments in wound edge keratinocytes: defining a potential role for keratin 16.

Abstract: Abstract. Injury to stratified epithelia causes a strong induction of keratins 6 (K6) and 16 (K16) in post-mitotic keratinocytes located at the wound edge. We show that induction of K6 and K16 occurs within 6 h after injury to human epidermis. Their subsequent accumulation in keratinocytes correlates with the profound reorganization of keratin filaments from a pan-cytoplasmic distribution to one in which filaments are aggregated in a juxtanuclear location, opposite to the direction of cell migration. This fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
385
3
12

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(437 citation statements)
references
References 72 publications
37
385
3
12
Order By: Relevance
“…The induction of these keratins occurs within 6 -12 h in suprabasal cells after epidermis full-thickness injury (McGowan and Coulombe, 1998a) and takes place at the mRNA level (Coulombe, 1997;Takahashi et al, 1998). With the accumulation of K6, K16, and K17, the protein levels of K1 and K10 are decreased (Mansbridge and Knapp, 1987;Paladini et al, 1996). First insights into the regulation of the K6 induction in wound healing came from in vitro studies with the use of human skin keratinocytes, which revealed AP-1 and epidermal growth factor-responsive elements in the human and bovine K6 promoter region (Jiang et al, 1993;Navarro et al, 1995).…”
Section: Mechanism Of K6 Inductionmentioning
confidence: 99%
“…The induction of these keratins occurs within 6 -12 h in suprabasal cells after epidermis full-thickness injury (McGowan and Coulombe, 1998a) and takes place at the mRNA level (Coulombe, 1997;Takahashi et al, 1998). With the accumulation of K6, K16, and K17, the protein levels of K1 and K10 are decreased (Mansbridge and Knapp, 1987;Paladini et al, 1996). First insights into the regulation of the K6 induction in wound healing came from in vitro studies with the use of human skin keratinocytes, which revealed AP-1 and epidermal growth factor-responsive elements in the human and bovine K6 promoter region (Jiang et al, 1993;Navarro et al, 1995).…”
Section: Mechanism Of K6 Inductionmentioning
confidence: 99%
“…During wound healing, keratinocytes at the wound edge undergo cell shape changes and become migratory (Gabbiani et al, 1978;Paladini et al, 1996) and changes in keratin expression take place (Mansbridge and Knapp, 1987). Suction blister (epidermal) wounds were therefore examined for changes in K15 expression, using LHK15 to monitor K15 expression at various time points up to 96 hours after injury.…”
Section: K15 Expression In Stressed and Pathological Human Epidermismentioning
confidence: 99%
“…For example, keratin 16 is expressed in native gingiva, but is absent in native skin (Figure 3). Furthermore, keratins 16 and 17 are described to be upregulated during wound healing as they disrupt the rigid structure of the epithelium, thus allowing keratinocytes to migrate over each other and over the connective tissue matrix (Paladini, Takahashi, Bravo, & Coulombe, 1996). Notably, both keratins were expressed in the midsections of the SS as well as the GS.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that these keratins may promote reorganization of the cytoplasmic array of keratin filaments (Paladini et al, 1996). This is an event that precedes the onset of keratinocyte migration into the wound site.…”
Section: Discussionmentioning
confidence: 99%